If f(x)=xx then find f′(3) Finding Differentiation: Notice that f(x) is provided and we need to find f′(3). To find f′(3) we must need to find f′(x) first. Therefore with the help fo differentiation we will find f′(x) and then we will substitute x=3 to find f′...
Answer to: If f(x) = 5x^2, find f'(3). By signing up, you'll get thousands of step-by-step solutions to your homework questions. You can also ask...
If f(x) = -2x^2 + 6, find the value of f(-3). Find f'(3), if f (x) = x^4 - 3 x. Given the function F(x) = f (g(x)) determine F'(3) given: f(3) = 3, f(2) = 9, f'(5) = 7, f'(3) = 6, g(3) = 5, g(6) = \frac{1}{2}, g'(5) = 4...
If f(x)=2x2, find f(3⋅8)−f(4)3⋅8−4: A 1⋅56 B 156 C 15⋅6 D 0⋅156 Video Solution Text SolutionGenerated By DoubtnutGPT The correct Answer is:D To solve the problem, we need to evaluate the expression f(3.8)−f(4)3.8−4 given that f(x)=2x2. 1. Ca...
If A={0,1,2,3,4}, then the number of proper subsets of A is 01:00 Doubtnut is No.1 Study App and Learning App with Instant Video Solutions for NCERT Class 6, Class 7, Class 8, Class 9, Class 10, Class 11 and Class 12, IIT JEE prep, NEET preparation and CBSE, UP Board, ...
1.if f(x)=x ln(x^2),then f ' (x)=?2.if f(x)=ln[x+4+e^(-3x)],then f ' (0) is?3.if f(x)=[e^(2x)]/2x,then f ' (x)=?4.if f=Arc tan(cosx),then dy/dx=?5.if g(x)=3^√(x-1) and f(x) is the inverse function of g(x),then f ' (...
1.if f(x)=x ln(x^2),then f ' (x)=?2.if f(x)=ln[x+4+e^(-3x)],then f ' (0) is?3.if f(x)=[e^(2x)]/2x,then f ' (x)=?4.if f=Arc tan(cosx),then dy/dx=?5.if g(x)=3^√(x-1) and f(x) is the inverse function of g(x),then f ' (x...
由f''(x)=2x+cos(x)两边积分得到 f'(x)=X的平方+sin(x) +a ,由于f'(0) =1,将x=0代入代人得到a=1 所以f'(x)=X的平方+sin(x) +1,将此式的两边积分得到 f(x)=1/3乘于X的立方-cos(x)+x+b,由于f(0)=1 ,将x=0代入得b=1 所以f(x)=1/3乘于X的立方-cos(x)...
If f(x)=x^2+ 1, then f(f(x))= ( ) A. x^4+1 B. x^4+2x^2+1 C. x^4+2x^2+2 D. x^4+x^2+1 E. x^4+2 相关知识点: 试题来源: 解析 C f(f(x))=f(x^2+1)=(x^2+1)^2+1=x^4+2x^2+1+1=x^4+2x^2+2...
andg(x)=−x,x∈R., then findf∘gandg∘f. Composite Function: f(x),g(x) (f∘g)(x) g(x) (g∘f)(x) f(x) g(x) Answer and Explanation:1 The given functions are, f(x)=x2+x,g(x)=x Thus, f∘g...